From strong leadership to active community engagement: effective resistance to illicit economies in Afro-Colombian collective territories (2020)
This paper studies the onset and recent expansion of illicit crops into the collective territories of rural Afro-Colombian communities in the Pacific region of Colombia. We analyze whether community organization and leadership can explain differences in the presence and expansion of coca crops in these territories. Following a mixed-method approach that combines the analysis of satellite imagery, semi-structured interviews and household surveys, our results suggest that community organization and leadership (as expressions of social capital) do explain differences in the expansion of illicit crops by enabling (or hindering) different forms of resistance. Investing in social capital is thus one way to reorient policy interventions, a goal to which the Colombian state can only partially contribute given its structural limitations.